Indigenous healers in a future mental health system: A case for cooperation - Korber, Ilana (PINS-Psychology in Society, 2025)
There has been a great deal of debate about the relative merits of western psychiatry and what is generally known as traditional medicine or healing. Numerous anthropologists, psychologists, psychiatrists and other interested parties have investigated the area. Some have suggested that western psychiatry has a lot to learn from traditional methods; others have argued that traditional medicine is primitive, even dangerous, and should have no place alongside the western system of healing. This paper argues that regardless of the position adopted in the debate, the de facto situation reveals that both systems are widely used in South Africa. Thus, in discussing a future mental health system, it would be inappropriate to disregard a system of healing which is not only popular but will also contribute to the provision of mental health facilities to as many South Africans as possible. It will be suggested that a high level of cooperation, rather than a hybrid psychiatric system, be developed. The need for cooperation is raised throughout the paper and is based on an appraisal of the relevant literature and an assessment of some of the issues which need to be discussed. The paper first takes a brief look at previous research on indigenous medicine. It then focuses on the use of indigenous healers in South Africa and observes that both indigenous and western systems are relied upon. The coexistence of the two systems in Southern Africa is then briefly addressed. Arising from the coexistence of these two systems the question of the professionalisation of indigenous healers in South Africa is discussed. Finally, the paper argues that cooperation between the two systems is required and some of the obstacles are raised.